Karumidze, Zurab and Wertsch James V. (Ed.) Enough. The Rose Revolution in the Republic of Georgia 2003 Nova Science Publishers New York, 2005 - Priego, Alberto (UNISCI Discussion Papers, 2005)
Sin resumen